Impact of Information Technologies on Adolescents' Health - A.V. Yeshchenko (Zaslavsky O.Yu., 2013)
The paper presents recent data concerning the impact of computer technologies, long Internet surfing, mobile phone use on adolescents' health. The development of addictive behaviors in adolescents - personal computer users is described. The recommendations concerning rational computer and mobile phone use by adolescents have been offered. A necessity of special doctors' training in medical and social assistance to adolescents has been accentuated.